Facilitators of and barriers to labor market participation among people with acquired deafblindness: A scoping review - Eline C. M. Heppe; Natascha S. Søndergaard; Emma Klaassen; Michelle Bak; Marleen Smits; Emma Vaillant (PLoS ONE, 2026)
This scoping review aims to identify factors that facilitate or hinder labor market participation of people with an acquired hearing and vision impairment, also called acquired deafblindness (ADB). For people with ADB, participation in society is not a given, and work is a key aspect of societal participation. A literature search was conducted in Web of Science, MEDLINE, and PsycINFO via Ovid. The studies included involved people with ADB, results on labor market participation, and a description of at least one facilitator or barrier. Of 2,548 articles identified, 13 met the inclusion and exclusion criteria. Using the International Classification of Functioning, Disability and Health (ICF) framework, 90 facilitators and 66 barriers were identified. Most facilitators and barriers were identified in the “ Environmental Factors ” domain, while the fewest facilitators were in the “ Body Structures and Body Functions ” and the fewest barriers in “ Personal Factors .” As more facilitators than barriers were identified, labor market participation could be improved for people with ADB. However, most barriers were found in the “ Services, Systems, and Policies ” subdomain, suggesting vocational rehabilitation services may not be as effective as intended. Further research is needed to explore these barriers and their impact on employment for people with ADB.